Improving The Efficiency of Prime-Motor Generators in PLTUAT the Panji Sugar Factory in Situbondo - Much Rizky Ubaidillah; Kartiko Ardi Widodo (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2026)
This observe goals to investigate generator performance in a steam era machine with the aid of using analyzing the connection among turbine strength and steam go with the drift versions at some stage in operation. Data series changed into carried out without delay on Tuesday, September 24, 2024, protecting steam inlet and outlet strain and temperature, steam go with the drift rate, and generator electric load each hour. This statistics changed into used to calculate turbine strength and generator performance beneathneath every working circumstance. The evaluation confirmed durations with the bottom performance, specifically at 6:00 AM and 10:00 AM, each of which had been under 70%. This circumstance changed into because of an imbalance among the turbine`s mechanical strength being too excessive in comparison to the generator's electric load. By adjusting steam go with the drift at some stage in those hours, turbine strength may be decreased to higher healthy load requirements, and generator performance will increase to attain the preferred minimal working limit. These findings verify that steam go with the drift law is an powerful operational step to optimize generator overall performance with out requiring adjustments to the turbine configuration. The effects of this observe are anticipated to function a reference in power control and performance development in steam-primarily based totally era systems.